Juvenile Selenium Deficiency Impairs Cognition, Sensorimotor Gating, and Energy Homeostasis in Mice - Kilonzo, Victor W.; Sasuclark, Alexandru R.; Torres, Daniel J.; Coyle, Celine; Pilat, Jennifer M.; Williams, Christopher S.; Pitts, Matthew W. (Frontiers in Nutrition, 2021)
Selenium (Se) is an essential micronutrient of critical importance to mammalian life. Its biological effects are primarily mediated via co-translational incorporation into selenoproteins, as the unique amino acid, selenocysteine. These proteins play fundamental roles in redox signaling and includes the glutathione peroxidases and thioredoxin reductases. Environmental distribution of Se varies considerably worldwide, with concomitant effects on Se status in humans and animals. Dietary Se intake within a narrow range optimizes the activity of Se-dependent antioxidant enzymes, whereas both Se-deficiency and Se-excess can adversely impact health. Se-deficiency affects a significant proportion of the world's population, with hypothyroidism, cardiomyopathy, reduced immunity, and impaired cognition being common symptoms. Although relatively less prevalent, Se-excess can also have detrimental consequences and has been implicated in promoting both metabolic and neurodegenerative disease in humans. Herein, we sought to comprehensively assess the developmental effects of both Se-deficiency and Se-excess on a battery of neurobehavioral and metabolic tests in mice. Se-deficiency elicited deficits in cognition, altered sensorimotor gating, and increased adiposity, while Se-excess was surprisingly beneficial.